Zwitterionic charged copolymer membranes

JP2022533557A5Active Publication Date: 2025-02-20TRUSTEES OF TUFTS COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021566176
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-05-10
Filing Date
2020-05-08
Publication Date
2025-02-20
Estimated Expiration
2040-05-08

Smart Images

  • Figure 2020231797000001
    Figure 2020231797000001
  • Figure 2020231797000002
    Figure 2020231797000002
  • Figure 2020231797000003
    Figure 2020231797000003
Patent Text Reader

Abstract

Disclosed are linear / random / statistical copolymers containing three types of monomer units: hydrophobic monomer units, zwitterionic monomer units, and charged or ionizable monomer units. Also provided are thin composite membranes whose separation-selective layers comprise the copolymers disclosed herein, and methods of using the same.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of U.S. Provisional Application No. 62 / 846,014, filed May 10, 2019, the contents of which are incorporated herein by reference in their entirety.

[0002] This invention was made with Government support under Grants 1508049 and 1553661 awarded by the National Science Foundation. The Government has certain rights in this invention. [Background technology]

[0003] Nanofiltration (NF) membranes are specified with an effective pore size of about 1 nm. They are typically used to remove divalent salts from water and wastewater streams in applications such as water softening. Almost all commercial NF membranes on the market today are equipped with a cross-linked polyamide separation selective layer prepared by interfacial polymerization. This separation selective layer chemistry has been in use for decades and as a result these commercial membranes are very well optimized and have excellent performance for removing the desired divalent salts. Prevention At the same time, it provides a moderately high water permeability.

[0004] However, polyamide separation selective layers also have significant limitations inherent to their chemical structure, such as lack of fouling resistance and chlorine resistance. In recent years, zwitterions have attracted extensive research in the membrane field due to their hydrophilicity and fouling resistance. Zwitterionic amphiphilic copolymers (ZACs) have been noted to self-assemble to create microstructures. Moreover, fouling-resistant membranes with effective pore sizes of about 1-2 nm can be achieved when ZACs are used as membrane separation selective layers. These membranes have also been shown to have high chlorine resistance.

[0005] However, an important feature of these membranes is that they have relatively low salt tolerance due to the overall neutral chemical nature of the membrane separation selective layer. Rejection rate Thus, ZAC offers promising fouling and chlorine resistance, and an effective pore size close to that of NF membranes, while preventionThe properties are insufficient to replace the commercially available NF membranes in most applications. Therefore, there is a need to develop high-performance membranes that do not have the aforementioned drawbacks. Summary of the Invention [Means for solving the problem]

[0006] Provided herein are copolymers that include multiples of each of three types of monomer units: hydrophobic monomer units, zwitterionic monomer units, and charged or ionizable monomer units. Preferably, the copolymers are linear, statistical, or random copolymers, or all of them. Also provided are thin composite membranes whose separation-selective layers consist of these copolymers. These membranes can be used in several aqueous separations, including, but not limited to, water treatment, water softening, wastewater treatment, and separation and purification of organic molecules in aqueous solutions. Due to the chemical nature of these copolymers, the membranes exhibit improved resistance to chemical degradation by chlorine and strong resistance to fouling.

[0007] In one aspect, provided herein is a copolymer comprising a plurality of zwitterionic monomer units, a plurality of charged / ionizable monomer units, and a plurality of hydrophobic monomer units.

[0008] In yet another aspect, provided herein is a composite membrane comprising a porous support and a membrane of a polymeric material, wherein the pore size of the porous support is greater than the effective pore size of the membrane of the polymeric material.

[0009] In another aspect, provided herein is a method for size-based selection or removal comprising contacting a solution containing a plurality of uncharged organic molecules of different sizes with a composite thin film disclosed herein.

[0010] In yet another aspect, provided herein is a method of charge-based selection or removal comprising contacting a solution containing a plurality of salts with a thin composite film disclosed herein. [Brief description of the drawings]

[0011] [Figure 1] Scheme showing the polymer structure / chemistry of a charged zwitterionic amphiphilic copolymer (CZAC), P(TFEMA-r-SBMA-r-MAA), and a schematic of its self-assembly upon coating onto a support to form a membrane separation selective layer featuring approximately 1-2 nm hydrophilic domains that act as a network of effective nanochannels lined with carboxylic acid groups. [Diagram 2] 1H NMR spectrum of PTFEMA-SBMA-MAA-B1 showing copolymerization. [Diagram 3] 1H NMR spectrum of PTFEMA-SBMA-MAA-B2 showing copolymerization. [Figure 4A] 1 shows an SEM image of an uncoated Trisep UE50 support membrane. [Figure 4B] 1 shows an SEM image of the PTFEMA-SBMA-MAA-B1 TFC membrane. [Figure 4C] 1 shows an SEM image of the PTFEMA-SBMA-MAA-B2 TFC membrane. [Figure 5A] 1 is a bar graph showing the rejection of neutral (Rib, RH, and VB12) and anionic (Na2SO4, MO, AB45) solutes by PTFEMA-SBMA, PTFEMA-SBMA-MAA-B1, and PTFEMA-SBMA-MAA-B2 membranes. [Figure 5B] 1 is a graph showing the rejection of sugars and dyes by membranes prepared as described in Example 2B. [Figure 6A] 1 is a bar graph showing the rejection of various salts at concentrations of 1 mM and 5 mM by PTFEMA-SBMA, PTFEMA-SBMA-MAA-B1, and PTFEMA-SBMA-MAA-B2 membranes. [Figure 6B] 1 is a graph showing the rejection of Na2SO4 (CFeed=5 mM) at various pH by PTFEMA-SBMA-MAA-B1. [Figure 6C]1 is a bar graph showing the rejection of various salts at 1 mM and 5 mM concentrations on PTFEMA-SBMA-MAA-B2. The rejection is matched to DSPM (for CFeed=1 mM: Dpore=1.95 nm, δeffective=20 μm, and X=21.4 mM. For Cfeed=5 mM: Dpore=1.95 nm, δeffective=20 μm, and X=60.4 mM). [Figure 7A] 1 is a bar graph showing the percent rejection of various neutral dyes. [Figure 7B] 1 is a bar graph showing the rejection of various anionic dyes and Na2SO4. [Figure 8A] FIG. 13 is a graph showing the oil emulsion fouling resistance of PTFEMA-SBMA-MAA-B2 membrane (stabilized by Span 80 neutral surfactant). [Figure 8B] FIG. 13 is a graph showing the oil emulsion fouling resistance of PTFEMA-SBMA-MAA-B2 membrane (stabilized by DC193 neutral surfactant). [Figure 8C] 1 is a graph showing the fouling resistance of CZAC membranes to BSA and CaCl mixtures (1.0 g / L BSA, 10 mM CaCl, pH=6.3, and J0 5.4LMH). A commercial NF membrane was used as a benchmark. [Figure 8D] 1 is a graph showing the fouling resistance of CZAC membranes to humic acid and alginate mixtures (1 g / L each, pH 4.5, J0=7.0 LMH). A commercial NF membrane was used as a benchmark. [Figure 9] 1 is a graph showing the permeance of PTSBMA-SBMA-MAA before and after Clorox treatment. [Figure 10] IR spectra showing the effect of chlorination on the bond chemistry of PTFEMA-SBMA-MAA-B2. FTIR spectra were acquired before and after immersion in sodium hypochlorite solution at pH 4.5, 2,000 ppm for 16 hours. [Figure 11]FIG. 13 is a graph showing the reconstitution of PTFEMA-SBMA-MAA-B1 upon exposure to PBS solution and the subsequent switchable flux behavior observed. [Figure 12A] FIG. 13 is a bar graph showing the reconstitution of PTFEMA-SBMA-MAA-B1 membrane with NaOH (aq) (pH=11). [Figure 12B] 1 is a bar graph showing the permeability coefficient of PTFEMA-SBMA membrane during filtration of NaOH (aq) (pH=11). [Figure 13] 1 is a bar graph showing the rejection of vitamin B12 and Na2SO4 before and after reconstitution with NaOH (aq). [Figure 14] 1 is a bar graph showing the relationship between membrane permeability coefficient and filtration ID (Table 5). [Figure 15] 1 is a bar graph showing the permeability coefficient of reconstituted PTFEMA-SBMA-MAA membranes in response to basic solutions containing calcium. [Figure 16] 1 is a graph showing the correlation between reaction mixture composition and the resulting terpolymer composition, indicating near random monomer sequencing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Taking advantage of the self-assembly properties of ZAC, this polymer family was modified to improve salt rejection. (Salt rejection rate)Membranes that combine NF-type selectivity with fouling resistance and chlorine resistance are disclosed by improving the selectivity of the membrane. Specifically, charged zwitterionic amphiphilic copolymers (CZACs) and membranes prepared with CZAC separation selective layers through scalable fabrication techniques are disclosed. CZACs are random or statistical terpolymers of three types of monomers: hydrophobic monomers, zwitterionic monomers, and acidic / ionizable monomers. Preferably, the copolymers are linear, random, and statistical copolymers. Due to the random / statistical architecture of the copolymers and zwitterionic-zwitterionic attractions, the terpolymers can self-assemble into a bicontinuous network of 1-2 nm hydrophilic (zwitterionic / charged) and hydrophobic nanodomains. Water and other solutes pass through the hydrophilic domains. The hydrophilic domains function as an effective network of nanochannels with charged walls. This allows the terpolymers to function as membrane separation selective layers. Hydrophilic nanochannels are net charged through ionization of the incorporated functional groups (e.g., deprotonation of acidic repeat units, protonation of amine groups, and dissociation of sulfonic acid groups) and allow the transport of charged solutes and salt ions. prevention Due to the presence of zwitterionic groups, these membranes are highly resistant to fouling. The use of novel polymer chemistry allows for high chlorine resistance, with no change in performance even after exposure to 32,000 ppm.hr of chlorine.

[0013] A family of polymeric materials is disclosed that includes a plurality of at least three types of repeat units: 1. Zwitterionic repeat units, which are smaller than the domain size, preferably less than 5 nm, preferably 0.6-3 nm, more preferably 0.6-2 nm, of water and aqueous solutions containing solutes. transparent This results in the formation of a bicontinuous network of hydrophilic / water-permeable nanodomains that act as pathways. 2. Chargeable or ionizable repeating units, which are exclusion It confers charge-based selectivity and ion-retention properties through a mechanism. 3. A relatively hydrophobic repeat unit that limits swelling of the polymer in water and confers stability to the polymer in an aqueous environment. The hydrophobic repeat unit is preferably derived from a monomer whose homopolymer is insoluble in water and has a glass transition temperature above the temperature of use (e.g., above room temperature).

[0014] The polymers, termed "charged zwitterionic amphiphilic copolymers" (CZACs), may be synthesized from vinyl monomers (e.g., acrylates, methacrylates, acrylamides, styrene derivatives, acrylonitrile) using well-known polymerization methods (e.g., free radical polymerization). The polymers incorporate the three types of repeat units in a more or less random / statistical order (rather than large blocks of individual monomers) and have molecular weights of 20,000 g / mol to 1,000,000 g / mol (preferably 40,000 g / mol, or 100,000 g / mol to 1,000,000 g / mol). Preferably, the copolymers are linear.

[0015] In a particular composition suitable for the applications / embodiments described below for the membrane selective layer, the CZAC comprises -30-80% by weight hydrophobic monomer, 1-40% by weight charged monomer, and 1-40% by weight zwitterionic monomer. In other applications, a wider range of compositions may be used.

[0016] Exemplary monomers for forming each type of repeat unit are listed below.

[0017] Zwitterion: Sulfobetaine methacrylate (SBMA) * ; methacryloxyphosphorylcholine (MPC); carboxybetaine methacrylate (CBMA); sulfobetaine-2-vinylpyridine; sulfobetaine-4-vinylpyridine; sulfobetaine-vinylimidazole; and several others that contain a sulfobetaine, carboxybetaine, or phosphorylcholine moiety.

[0018] Charged / Ionizable: Methacrylic Acid (MAA) *;acrylic acid;styrene sulfonic acid;methacrylates, acrylates, acrylamides, or styrene derivatives containing carboxylic acids, sulfonic acids, amines, phosphates, or other ionizable / charged groups.

[0019] Relatively hydrophobic: 2,2,2-trifluoroethyl methacrylate (TFEMA) * other fluorinated acrylates, methacrylates, and acrylamides (eg, pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, pentafluorophenyl methacrylate); styrene; methyl methacrylate; acrylonitrile; and other monomers meeting the above criteria.

[0020] The usefulness of the polymeric materials is discussed below, particularly with respect to their use as selective layers in membrane separations, however, they may also be useful in other applications (e.g., additives in membrane manufacture, compatibilizers).

[0021] The CZAC may be coated onto a porous support by methods understood in the membrane industry (e.g., blade coating, non-solvent induced phase separation (NIPS), spray coating). This results in a thin film composite (TFC) that includes at least two layers: a porous support with coarse pores that provide mechanical integrity; and a thin layer of CZAC (preferably less than 10 μm thick, more preferably less than 3 μm or less than 1 μm thick) that serves as the "separation selective layer" of the membrane. In this embodiment, the CZAC layer typically includes a continuous dense layer of CZAC (i.e., not the usual "through holes" that provide a path for water permeation (except for occasional defects that may undesirably occur during processing)); in other words, water will pass through the CZAC as the primary transport mechanism, rather than through the pores / holes in the CZAC. transparent It is necessary to.

[0022] The resulting membrane exhibits size-based separation of neutral organic molecules, but with a higher separation rate for charged solutes than for neutral solutes. Rejection rateThis quality is useful in some applications where size-based separation is insufficient. For example, when complete or partial removal of contaminants is required, the size-based and charge-based separation offered by these membranes can be used to advantage. prevention The combination of these can improve the quality of excretion. Alternatively, these membranes can separate two organic solutes (e.g., amino acids, drug compounds) that differ in the presence of charged groups from each other.

[0023] Current membranes can be modified and formulated to improve salt rejection, address reverse osmosis (RO) / desalination processes and forward osmosis (EO), or access slightly larger pore sizes to become charge selective and rigorous ultrafiltration (UF) membranes.

[0024] Commercially available NF and RO / EO membranes are almost universally equipped with a cross-linked polyamide separation selective layer. Such membranes have two major problems: first, they are prone to fouling and require several pretreatment steps, affecting the cost and energy efficiency of the entire desalination process. Second, the membranes are highly sensitive to chlorine, which reacts with the separation selective layer. Chlorination is typically used to kill microorganisms in the water entering the desalination plant to prevent biofouling. Because commercial NF and RO membranes are sensitive to chlorine, the water is dechlorinated before being fed to the NF or RO unit and chlorinated again before being sent to the customer.

[0025] The current membranes avoid both of these problems: the zwitterionic groups are known and demonstrated to be highly resistant to fouling. The membranes have been shown to be extremely resistant to fouling from organic streams. Additionally, the constituent polymers are inherently resistant to attack by chlorine. The membranes have been shown to be stable to commercial chlorine bleaches.

[0026] Upon exposure to high pH buffers, membranes may undergo pore reorganization. Upon exposure to high pH buffers, membranes with some CZAC separation selective layers undergo a one-time irreversible and stable reorganization with a small increase in pore size. transparent This indicates increased sexual activity. - CZAC derived from hydrophobic monomer TFEMA, zwitterionic monomer SBMA, and ionizable monomer MAA can be synthesized by free radical polymerization in multiple monomer ratios. -The copolymer self-assembles to create a network of hydrophilic nanodomains that act as pathways for water permeation. - This membrane can be coated onto a commercially available coarse pore membrane as a porous support to create a thin film composite (TFC). - The membrane is comparable to commercially available RO and NF membranes Permeability coefficient (defined as flux / applied pressure difference), which can be further improved by reducing the coating thickness and modifying the polymer formulation. - The membrane exhibits size-based selectivity between uncharged organic molecules, including vitamin B12 and β-cyclodextrin, with approximately 92% prevention Shows the rate. prevention The model yields an estimated effective pore size of approximately 2 nm, which can be tuned to lower and higher values ​​by polymer chemistry and other methods (1-5 nm appears to be an accessible range). - The membrane exhibits significantly higher ion transport properties for charged solutes than for uncharged solutes of similar size. Rejection rate Shows. - This membrane is about 95% NaSO4 prevention The results show significant salt rejection rates, including 100% sulphuric acid (SA) and 100% sulphuric acid (SO) membranes, which are comparable to some NF membranes. - The polymer is stable even when exposed to chlorine bleach (e.g., at pH 4). - The membrane is highly resistant to fouling by oil emulsions. - When exposed to a buffer with a relatively high pH, ​​the membrane prevention The membrane exhibits a one-time increase in flux with a slight decrease in the rate. The new flux and pore size are stable; the change is irreversible. Furthermore, the membrane achieves switchable flux in different ionic solutions that can be controlled by the cations present in the solution.

[0027] In one aspect, provided herein is a copolymer comprising a plurality of zwitterionic monomer units, a plurality of charged / ionizable monomer units, and a plurality of hydrophobic monomer units.

[0028] In some embodiments, the molecular weight of the copolymer is from 20,000 g / mol to 1,000,000 g / mol. In some embodiments, the molecular weight of the copolymer is from 40,000 g / mol to 1,000,000 g / mol. In some embodiments, the molecular weight of the copolymer is from 100,000 g / mol to 1,000,000 g / mol.

[0029] In some embodiments, the zwitterionic monomeric units comprise 1-40% by weight of the copolymer. In some embodiments, the charged / ionizable monomeric units comprise 1-40% by weight of the copolymer. In some embodiments, the hydrophobic monomeric units comprise 30-80% by weight of the copolymer.

[0030] In some embodiments, each of the zwitterionic monomer units is formed from a monomer comprising a sulfobetaine, carboxybetaine, or phosphorylcholine moiety. In some embodiments, each of the zwitterionic monomer units is formed from a monomer selected from the group consisting of sulfobetaine methacrylate (SBMA), methacryloxyphosphorylcholine (MPC), carboxybetaine methacrylate (CBMA), sulfobetaine-2-vinylpyridine, sulfobetaine-4-vinylpyridine, and sulfobetaine-vinylimidazole. In some embodiments, each of the zwitterionic monomer units is formed from sulfobetaine methacrylate (SBMA).

[0031] In some embodiments, each of the charged / ionizable monomeric units is formed from a monomer selected from the group consisting of methacrylate, acrylate, acrylamide, or styrene derivatives that include a carboxylic acid, sulfonate, phosphate, or amine moiety. In some embodiments, each of the charged / ionizable monomeric units is formed from a monomer selected from the group consisting of methacrylic acid (MAA), acrylic acid, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, styrene sulfonate, 3-sulfopropyl acrylate, 3-sulfopropyl methacrylate, 2-acrylamido-2-methyl-1-propanesulfonic acid, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 2-aminoethyl methacrylate, [2-(methacryloyloxy)ethyl]trimethylammonium chloride, [2-(a-methyl)ethyl]ethyl acrylate ... In some embodiments, the charged / ionizable monomer units are formed from monomers selected from the group consisting of (3-acrylamidopropyl)trimethylammonium chloride, N-[3-(dimethylamino)propyl]methacrylamide, 2-isopropenylaniline, 4-[N-(methylaminoethyl)aminomethyl]styrene, and (vinylbenzyl)trimethylammonium chloride. In some embodiments, each of the charged / ionizable monomer units is formed from methacrylic acid (MAA).

[0032] In some embodiments, each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of styrene, methyl methacrylate, acrylonitrile, fluoroalkyl acrylate, fluoroaryl acrylate, fluoroalkyl methacrylate, fluoroaryl methacrylate, fluoroalkyl acrylamide, and fluoroaryl acrylamide. In some embodiments, each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of fluoroalkyl acrylate, fluoroaryl acrylate, fluoroalkyl methacrylate, fluoroaryl methacrylate, fluoroalkyl acrylamide, and fluoroaryl acrylamide. In some embodiments, each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of 2,2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, and pentafluorophenyl methacrylate. In some embodiments, each of the hydrophobic monomer units is formed from 2,2,2-trifluoroethyl methacrylate (TFEMA).

[0033] In some embodiments, the hydrophobic monomeric units are characterized in that homopolymers formed from the hydrophobic monomeric units have a glass transition temperature above room temperature.

[0034] In some embodiments, the copolymer is a random copolymer.

[0035] In some embodiments, the copolymer is a statistical copolymer.

[0036] In some embodiments, the copolymer is a linear copolymer.

[0037] In some embodiments, the copolymer is poly((sulfobetaine methacrylate)-random-(methacrylic acid)-random-(2,2,2-trifluoroethyl methacrylate)).

[0038] In another aspect, provided herein is a polymeric material comprising a plurality of copolymers, hi some embodiments, the polymeric material is in the form of a thin film.

[0039] In yet another aspect, provided herein is a composite membrane comprising a porous support and a membrane of a polymeric material, wherein the pore size of the porous support is greater than the pore size of the membrane of polymeric material.

[0040] In some embodiments, the thin film of polymeric material has a thickness of from 1 nm to 10 μm. In some embodiments, the thin film of polymeric material has a thickness of from 1 nm to 3 μm. In some embodiments, the thin film of polymeric material has a thickness of from 1 nm to 1 μm.

[0041] In some embodiments, the thin film of polymeric material has an effective pore size of 0.1 to 5 nm. In some embodiments, the thin film of polymeric material has an effective pore size of 0.6 to 3 nm. In some embodiments, the thin film of polymeric material has an effective pore size of 0.6 to 2 nm.

[0042] In some embodiments, the composite membrane exhibits resistance to fouling by oil emulsions.

[0043] In some embodiments, the composite films are stable upon exposure to chlorine bleach (eg, at pH 4).

[0044] In some embodiments, the composite thin film undergoes a one-time, irreversible change in pore size upon exposure to a high pH buffer.

[0045] In some embodiments, the composite thin film exhibits size-based selectivity between uncharged organic molecules.

[0046] In some embodiments, the composite thin film comprises a charged solute and a salt. prevention do.

[0047] In another aspect, provided herein is a method for size-based selection or removal comprising contacting a solution containing a plurality of uncharged organic molecules of different sizes with a composite thin film disclosed herein.

[0048] In yet another aspect, provided herein is a method of charge-based selection or removal comprising contacting a solution containing a plurality of salts with a thin composite film disclosed herein. EXAMPLES

[0049] In order that the invention described herein may be more fully understood, the following examples are set forth. The examples described in this application are provided to illustrate the compounds, compositions, materials, devices, and methods provided herein, and should not be construed in any way as limiting the scope thereof.

[0050] Example 1. Synthesis of poly(trifluoroethyl methacrylate)-random-poly(sulfobetaine methacrylate)-random-poly(methacrylic acid) (PTFEMA-SBMA-MAA) Example 1A: Synthesis of PTFEMA-SBMA-MAA-B1 In this example, a random / statistical terpolymer of monomers trifluoroethyl methacrylate (TFEMA), sulfobetaine methacrylate (SBMA), and methacrylic acid (MAA) (these three-component terpolymers are commonly referred to as PTFEMA-SBMA-MAA) was synthesized as follows. First, TFEMA and MAA were purified using a basic alumina column. Then, DMSO (80 mL), purified TFEMA (5.49 g), SBMA (2.61 g), purified MAA (1.11 g), LiCl (0.090 g), and AIBN (11 mg) were added to a 250 mL flat-bottom reaction flask, which was then sealed with a rubber septum. The mixture was then stirred at room temperature for 2 days to dissolve the zwitterionic monomers. The flask was then sealed with a rubber septum and purged with N2 for 40 min, followed by immersion in a 70 °C oil bath with stirring. After 20 hours, the reaction was stopped by exposure to air and addition of MEHQ (0.5 g). The viscous polymer solution was then poured into 800 mL of a mixture of ethanol and hexane (1:1 by volume) for precipitation. The polymer was then cut into small pieces and washed by stirring in 800 mL of a mixture of ethanol and hexane (1:1 by volume) for more than 12 hours. This washing cycle was repeated twice. The polymer was then dried under a hood for about a week and finally dried in a vacuum oven at 50 °C for more than 24 hours. The yield was calculated to be 38%, as determined by the weight of the dried polymer. This polymer is called PTFEMA-SBMA-MAA-B1. The composition of the purified polymer is: 1 From the H-NMR spectrum (FIG. 2), the composition was calculated by integration of three sets of peaks: (1) c'', (2) e', and (3) c,c'. The composition was calculated to be 61.9 wt% TFEMA, 31.7 wt% SBMA, and 6.4 wt% MAA.

[0051] Example 1B: Synthesis of PTFEMA-SBMA-MAA-B2 In this example, a random / statistical terpolymer of TFEMA, SBMA, and MAA was synthesized as follows. First, SBMA (2.80 g) and DMSO (87 mL) were added to a 250 mL flat-bottom reaction flask. The temperature was raised to 70 °C to dissolve the zwitterionic monomers and then allowed to return to room temperature. During this cool-down period, both TFEMA and MAA were purified using a basic alumina column (VWR). Following this, purified TFEMA (4.49 mL), purified MAA (1.86 mL), LiCl (0.10 g), and AIBN (9.8 mg) were added to the reaction flask. The flask was then sealed with a rubber septum and purged with N2 for 30 min before being immersed in a 70 °C oil bath with stirring. After 20 h, the reaction was quenched by exposing the reaction to air and adding MEHQ (0.7 g) dissolved in approximately 5 mL of DMSO. The viscous polymer solution was then poured into a 900 mL mixture of ethanol and hexane (1:1 volume ratio) for precipitation. The polymer was then cut into small pieces and washed with 900 mL of a mixture of ethanol and hexane (1:1 volume ratio) by stirring for 12 hours. This washing cycle was repeated three times. The polymer was then dried under a hood for about a week and finally dried in a vacuum oven at 50 °C for 4 days. The yield was calculated to be 60%, as determined by the weight of the dried polymer. This polymer is called PTFEMA-SBMA-MAA-B2. The composition of the purified polymer is: 1 From the H-NMR spectrum (FIG. 3), the composition was calculated by integration of three sets of peaks: (1) c'', (2) e', and (3) c,c'. The composition was calculated to be 52.2 wt% TFEMA, 34.9 wt% SBMA, and 12.9 wt% MAA.

[0052] Example 2. Polymer architecture From the data in Figure 16, it can be inferred that the terpolymers have a nearly random monomer sequence. The composition of the terpolymer was similar to the initial reaction conditions, with a yield of -70%. This is in contrast to the block architecture typically associated with self-assembling copolymers. There are strict kinetic requirements for a terpolymer to be truly random (all six reactivity ratios equal to 1), and it is possible that the terpolymers may be somewhat stepwise and / or blocky. However, in the field, the term "random" is not strictly applied. Therefore, to best convey the polymer architecture to a wide audience, the terpolymers are referred to as being random.

[0053] Example 3. Formation of a thin membrane composite (TFC) using a PTFEMA-SBMA-MAA terpolymer separation selective layer Example 3A. Formation of TFC Membrane from PTFEMA-SBMA-MAA-B1 In this example, a TFC membrane was prepared using the polymer described in Example 1A. The copolymer was first dissolved in trifluoroethanol (TFE) at 0.11 g copolymer / mL TFE. The solution was then filtered using a 1 μm glass syringe filter, degassed by heating to 50° C. for 1 h, and cooled back to room temperature. The copolymer solution was then coated onto a PES ultrafiltration support membrane (Trisep UE50) using a Gardco wire-wound rod (wire size 2 1 / 2, depositing a 6 μm wet membrane). After coating, the coated membrane was quickly immersed in a non-solvent bath of isopropyl alcohol (IPA) for 20 min, followed by immersion in deionized water. This procedure resulted in a TFC membrane whose separation selective layer was the PTFEMA-SBMA-MAA-B1 terpolymer described in Example 1A.

[0054] Example 3B. Formation of TFC Membrane from PTFEMA-SBMA-MAA-B2 In this example, a membrane was prepared using the polymer described in Example 1B. First, the copolymer was dissolved in trifluoroethanol (TFE) at 0.11 g copolymer / mL TFE. The solution was then filtered using a 1.2 μm glass syringe filter, degassed by heating to 50° C. for 1 h, and cooled back to room temperature. The copolymer solution was then coated onto a PES ultrafiltration support membrane (Trisep UE50) using a Gardco universal blade applicator with a gate setting of 20 μm. After coating, the film of the polymer solution was allowed to evaporate for 15 seconds. The coated membrane was then immersed in a non-solvent bath of isopropyl alcohol (IPA) for 20 minutes, followed by immersion in deionized water. This procedure resulted in a thin film composite (TFC) in which the separation selective layer was the PTFEMA-SBMA-MAA-B2 terpolymer described in Example 1B. Scanning electron microscopy (SEM) was used to observe cross sections of the TFC membranes described in Examples 2A and 2B, which allowed the thickness of the selective layer and the morphology of the membrane to be analyzed. To prepare the samples, membrane sections were freeze-fractured and sputter-coated with gold-palladium. SEM images of the membrane cross sections were acquired using a Phenom G2 pure tabletop SEM at a 5 kV setting. Figures 4A, 4B, and 4C show SEM images of an uncoated Trisep UE50 membrane (support), the TFC membrane of Example 2A, and the TFC membrane of Example 2B. For each of the two examples, the separation selective layer is observed to be dense and 0.5-1 μm thick.

[0055] Example 4. PTFEMA-SBMA-MAATFC membrane Water permeability coefficient In this example, the pure water of the membranes described in Examples 2A and 2B Permeability coefficient was measured and compared with a membrane prepared from PTFEMA-SBMA. A 10 mL Amicon 8010 stirred cell in dead-end mode was used to perform the experiments. The area of ​​the membrane piece was 4.1 cm 2 The stirring speed was 500 RPM, and the pressure was 30 psi for the PTFEMA-SBMA-MAA-B1 membrane and 50 psi for the PTFEMA-SBMA-MAA-B2 membrane. Permeability coefficient To measure the time, we used an Ohaus Scout Pro scale connected to a computer. transparent Synchronous measurement of the mass of the membrane allows the measurement of the membrane flow rate, which Permeability coefficient The PTFEMA-SBMA-MAA-B1 and PTFEMA-SBMA-MAA-B2 membranes were Permeability coefficient , respectively 1.7L / m 2 .h.bar (abbreviated as LMH / bar) and 2.5LMH / bar (Table 1). [Table 1]

[0056] Example 5. Neutral solutes with PTFEM-SBMA-MAATFC membrane prevention In this example, the membrane described in Example 3B was used to filter various neutral solutes. The objectives of these experiments were: (1) to demonstrate the ability of the membrane described in Example 3B to filter small neutral molecules from solution, and (2) to establish the effective pore size of the membrane described in Example 3B.

[0057] Filtration experiments were performed using a 10 mL Amicon 8010 stirred cell in dead-end mode. The membrane strip area was 4.1 cm. 2 , the stirring speed was 500 RPM, and the pressure was 50 psi for all experiments. transparent Discard the first 1.5 mL of permeate and add the next 0.7 mL. transparent The solution was collected for concentration measurement. transparent Liquor concentrations were measured using chemical oxygen demand (COD) for sugars and UV-vis spectroscopy for pigments.

[0058] FIG. 5B shows the structure of neutral sugar and neutral dye molecules. prevention Size selectivity was observed for the neutral solutes tested, with the largest size selectivity observed for vitamin B12 (hydrated diameter 1.48 nm) and β-cyclodextrin (hydrated diameter 1.54 nm). prevention The conversion rate was about 92% (Table 2). preventionBy fitting the index data to the extended Nernst Planck equation with steric hindrance boundary conditions, the effective pore size was calculated to be 1.95 nm. [Table 2]

[0059] Example 6. Salt with PTFEMA-SBMA-MAA TFC membrane prevention In this example, various ionic solutes were filtered using the TFC membrane described in Example 3B. The objectives of these experiments were: (1) to demonstrate the ability of membranes prepared as described in Example 3B to filter salts from solution, and (2) to demonstrate the ability of membranes prepared as described in Example 3B to selectively filter ionic species while allowing neutral solutes of the same size to pass through.

[0060] Filtration experiments were performed using a 10 mL Amicon 8010 stirred cell in dead-end mode. The membrane strip area was 4.1 cm. 2 , the stirring speed was 500 RPM, and the pressure was 50 psi for all experiments. transparent Discard the first 1.5 mL of the solution and add the next 0.7 mL. transparent The solution was collected for concentration measurement. transparent The solution concentration was measured using a conductivity meter, and the data is shown in Table 3.

[0061] FIG. 6A shows that the PTFEMA-SBMA-MAA-B1 and PTFEMA-SBMA-MAA-B2 membranes have a greater ability to react with charged solutes than the PTFEMA-SBMA membrane. prevention This shows that the neutral solute prevention was comparable for all three membranes, this finding is evidence that MAA confers anion selectivity to the CZAC membrane. prevention The rate was in the range of 93-95% for Na2SO4 and 95% for CaSO4. prevention The rate ranges from 40 to 70%, and NaCl prevention The rates ranged from 30 to 60%.

[0062] To test the hypothesis that deprotonated MAA confers charge selectivity to the membrane, Na2SO4 is filtered at various pHs (Figure 6B). If deprotonated MAA is responsible for the anion selectivity, selectivity should disappear in acidic conditions. As expected, R(Na2SO4) is observed to decrease with decreasing pH, which can be explained by a shift in the equilibrium from deprotonated to protonated MAA. The decrease in selectivity only starts in earnest below pH 5.0, suggesting that the effective pKa of MAA is below about 4.0 in this system (pKa was fitted to 3.72 using the Donnan steric pore model combined with the Henderson-Hasselbalch equation; see Supplementary Material).

[0063] The effective pKa < 4.0 is well below the reported pKa of 4.78 for the MAA monomer, which means that MAA is approximately 10 times more reactive when incorporated into CZAC nanostructures than in free solution, which is contrary to expectations since confinement has generally been shown to result in a decrease in the reactivity of MAA.

[0064] Figure 6C shows the charge of a solute. prevention First, Figure 6C shows two noteworthy performance characteristics of the PTFEMA-SBMA-MAA-B2 membrane: (1) 96% of both 1 mM (142 ppm) Na2SO4 and 1 mM (110 ppm) Li2SO4 solutions. prevention (2) 93% of both 5 mM (710 ppm) Na2SO4 and 5 mM (550 ppm) Li2SO4 solutions prevention Rate (Table 3). CaSO4 and MgSO4 prevention The ratio is in the range of 40-70%, and NaCl and LiCl prevention The rate was in the range of 30-60%. prevention decreased with increasing feed concentration, which is consistent with Donnan exclusion The results are consistent with those of various salt species. prevention is that a combination of transport hindrance, steric exclusion, and Donnan equilibrium contribute to the transport of solutes through a charged membrane. preventionThe Donnan cubic pore model is a transport model that explains how prevention The ability of the membrane to filter ionic species while allowing neutral solutes of the same size to pass can be seen by comparing Figures 5 and 6C. Small ionic species (the hydrated diameter of sulfate is 0.46 nm; the hydrodynamic diameter of all ions tested is less than 0.7 nm) are filtered by the membrane. prevention whereas neutral solutes with hydration diameters below 1.0–1.5 nm were minimal. prevention Not done. [Table 3]

[0065] Example 7. Removal of dye and Na2SO4 by PTFEMA-SBMA-MAA TFC membrane compared to PTFEMA-r-SBMA TFC membrane prevention rate In this example, the dye and Na2SO4 were mixed using the TFC membrane prepared in Example 3A. prevention The PTFEMA-r-SBMA TFC membrane (referred to as PTFEMA-SBMA) was prevention The synthesis of PTFEMA-SBMA and the fabrication of PTFEMA-SBMA TFC membranes can be found elsewhere. Herein, we note that the main difference between PTFEMA-SBMA and PTFEMA-SBMA-MAA membranes is the lack of MAA in PTFEMA-SBMA membranes, which results in a higher permeability of charged solutes. prevention Note that the rate should be lower. The objectives of these experiments were: (1) to demonstrate the ability of the PTFEMA-SBMA-MAA-B1 membrane to filter dye from solution, a property that may be useful in applications such as dye removal in the textile industry; and (2) to further demonstrate the charge selectivity observed in the PTFEMA-SBMA-MAA TFC membrane, with the PTFEMA-SBMA TFC membrane serving as a suitable control.

[0066] Filtration experiments were carried out using a 10 mL Amicon 8010 stirred cell in dead-end mode. The membrane strip area was 4.1 cm. 2, the stirring speed was 500 RPM, and the pressure was 27 psi for all experiments. transparent The first 1.8 mL of the solution was discarded and the next 0.7 mL was collected. transparent The concentration of the solution was measured. transparent The solution concentrations were measured using UV vis spectroscopy for the dyes and conductivity for Na2SO4. The diameter of the dye molecules is the area in which the dye molecules are packed into a volume, V molar The sphere was assumed to be V. molar is the molar volume of the dye molecule; the molar volumes of the dyes were obtained using Molecular Modeling Pro software in ChemSW.

[0067] Figures 7A and 7B show the results of the reaction of various dyes with Na2SO4. prevention Table 4 shows the abbreviations, calculated diameters, charges, and fractions of solutes from the PTFEMA-SBMA-MAA-B1 and PTFEMA-SBMA membranes. prevention The rate of neutral dyes is summarized below. prevention The permeability of anionic solutes by the PTFEMA-SBMA-MAA-B1 membrane was similar to that of the PTFEMA-SBMA membrane, indicating similar effective pore sizes. prevention The rate of PTFEMA-SBMA membrane prevention This indicates that the membrane made from CZAC has a higher ion transport rate for charged solutes than the membrane made from the copolymer of zwitterionic and hydrophobic monomers only. prevention Furthermore, the kinetics of the charge transport in the prevention This can be explained by the presence of MAA in the PTFEMA-SBMA-MAA-B1 copolymer: MAA is a weak acid and acquires a negative charge upon deprotonation in aqueous solution. If MAA is incorporated into the zwitterionic domains of the self-assembled PTFEMA-SBMA-MAA-B1 separation selective layer, it can impart a negative charge to the nanochannels of the membrane. This was reported by Donnan exclusion Despite the well-documented phenomenon known as prevention This results in an increase in the rate. [Table 4]

[0068] Example 8. Fouling resistance of PTFEMA-SBMA-MAA TFC membrane Zwitterions are among the most fouling-resistant materials currently known. This is because the adsorption events on the contaminant surface that constitute fouling are limited by the strong hydration shell that surrounds the zwitterion (simulations show that ΔG hydration -500 kJ / mol). Previous studies have shown that membranes made of random zwitterionic copolymers are highly resistant to fouling, proving that zwitterions can still act as antifoulants from within the membrane nanostructure. To test whether this rule also applies to CZAC membranes, dead-end filtration with various model foulants is performed. A commercial NF membrane was used as a benchmark. The membrane was allowed to foul for 24 hours, and the initial flux of the CZAC membrane was consistent with that of the benchmark.

[0069] In this example, the fouling resistance of the PTFEMA-SBMA-MAA-B2 membrane described in Example 3B was measured using an oil-in-water emulsion, with the objective of demonstrating that the membrane is resistant to fouling, an important property for membranes to withstand fouling-prone materials.

[0070] Fouling experiments were performed using a 10 mL Amicon 8010 stirred cell in dead-end mode. The membrane pieces had an area of ​​4.1 cm. 2 The stirring speed was 500 RPM and the pressure was 50 psi for all experiments. Permeability coefficient To measure the time, we used an Ohaus Scout Pro scale connected to a computer. transparent Synchronous measurement of the mass of the object allows measurement of the membrane flow rate and Permeability coefficient We were able to calculate the following. Permeability coefficient is the average DIW before the membrane is introduced into the pollutant. Permeability coefficient Divided by, normalized Permeability coefficient The oil emulsion is composed of surfactant, oil, and water.<high>The stabilized emulsions were prepared by blending for 5 min at 37 °C for 1 min. The surfactant:oil mass ratio in the stabilized emulsion was 1:9 and the oil concentration was 1500 mg / L. Span80 surfactant was used for one fouling experiment and DC193 surfactant was used for the other fouling experiment.

[0071] Figures 8A and 8B show the two fouling experiments carried out above, both of which demonstrate that the PTFEMA-SBMA-MAA-B2 membrane is resistant to fouling.

[0072] FIG. 8C shows the fouling resistance of PTFEMA-SBMA-MAA-B1 to BSA / CaCl2 (1000 ppm and 10 mM, respectively), with NP30 (Microdyne; PES) serving as a control. BSA is a common model protein contaminant, and calcium salt was added to enhance its adsorption tendency. PTFEMA-SBMA-MAA-B1 was found to be significantly less fouling than NP30 throughout the 24-h fouling experiment. After a brief rinsing of the membrane, PTFEMA-SBMA-MAA-B1 fully recovered flux, confirming that the adsorption event was reversible. In contrast, NP30 fouled irreversibly.

[0073] FIG. 8D shows the fouling resistance of PTFEMA-SBMA-MAA-B2 to humic acid / alginate (1000 ppm each) along with UA60 (Trisep; PA) serving as a control. The pH was lowered to 4.5 with HCl to increase the adsorption tendency. PTFEMA-SBMA-MAA-B2 fouled less than UA60 throughout the 24-hour fouling experiment. Immediately after a brief rinse, PTFEMA-SBMA-MAA-B1 showed a recovery of 93% of the initial flux, Permeability coefficient After 5 hours, it returned to 96% of its initial value. UA60 showed a large initial decrease (82% recovery immediately after rinsing) and finally reached a recovery of 93% after 13 hours.

[0074] Example 9. Chlorine resistance of PTFEMA-SBMA-MAA-B1 TFC membrane In this example, PTFEMA-SBMA-MAA-B1 membranes were exposed to a solution containing a chlorination solution prepared by diluting commercial Clorox bleach and adjusting the pH to an acidic value according to commercial cleaning procedures. The purpose is to show that the PTFEMA-SBMA-MAA-B1 membrane is resistant to chlorine, which allows the membrane to be cleaned with sodium hypochlorite, a common disinfectant. Polyamide membranes, a staple of the NF market, are not stable when exposed to chlorine, which is a major drawback of this technology.

[0075] To carry out the experiments, a 10 mL Amicon 8010 stirred cell in dead-end mode was used. The membrane pieces had an area of ​​4.1 cm. 2 The stirring speed was 500 RPM and the pressure was 50 psi. Permeability coefficient To measure the time, we used an Ohaus Scout Pro scale connected to a computer. transparent Synchronous measurement of the mass of the object allows measurement of the membrane flow rate and Permeability coefficient It was possible to calculate the deionized water Permeability coefficient was measured as described above. The chlorination solution was prepared by diluting commercial Clorox laundry bleach with deionized water and adjusting the pH to 4 to ensure that the majority of the hypochlorite was hypochlorous acid. The final HClO concentration was estimated to be approximately 15,000 mg / L. The membrane strips were exposed to this solution for 1-2 hours. Permeability coefficient was measured again.

[0076] Figure 9 shows that the membrane was not damaged even after treatment with a chlorinated solution. Permeability coefficient shows no change, indicating that the film is stable when exposed to chlorine. Figure 10 shows the effect of chlorination on the chemistry of the PTFEMA-SBMA-MAA-B2 bond. FTIR spectra acquired before and after immersion in a 2,000 ppm sodium hypochlorite solution at pH 4.5 for 16 hours show that the structure remains intact before and after exposure. [Table 5]

[0077] Example 10. Reconstitution of bases observed in PTFEMA-r-SBMA-r-MAATFC membranes In this example, the irreversible response of PTFEMA-SBMA-MAA-B1 membranes to bases (termed base reconstitution) was investigated. The aim was to reveal the unique response behavior of membranes derived from this novel material. Filtration experiments were carried out using a 10 mL Amicon 8010 stirred cell in dead-end mode. The area of ​​the membrane pieces was 4.1 cm 2 , the stirring speed was 500 RPM, and the pressure ranged from 30 to 50 psi for all experiments.

[0078] FIG. 11 shows the reconstitution of base to an alkaline buffer system (PBS, pH=7.4) of the PTFEMA-SBMA-MAA-B1 membrane. Upon initial exposure to 10 mM PBS solution, Permeability coefficient increased from an initial value of about 1.8 LMH / bar to about 2.8 LMH / bar. When the membrane was in contact with DIW, Permeability coefficient increased to about 5.1 LMH / bar in distilled water (DIW). After reconstitution of the bases, Permeability coefficient can reversibly and rapidly switch between 5.1 LMH / bar in DIW and 2.8 LMH / bar in PBS. There is evidence that TFC membranes with separation selective layers consisting only of hydrophobic and zwitterionic monomers do not show such a response to PBS. 4

[0079] In the reconstruction seen in Figure 11, HPO4 2- Deprotonation of acidic MAA protons by PBS (the strongest base in PBS) was suspected to be the driving force. To test this hypothesis, the following experiments were performed. First, vitamin B12 prevention rate, Na2SO4 prevention The initial PTFEMA-SBMA-MAA-B1 membrane Permeability coefficient Then, NaOH was added to the (水溶液) (pH 11, 0.1 mM) was filtered through a membrane, while Permeability coefficient The membranes were then returned to DIW to see if the same irreversible response occurred. prevention Rate and Na2SO4 prevention The rate was measured again. Figures 12A and 12B show the results of this experiment. (水溶液) This indicates that NaOH can indeed cause the base reorganization observed in PBS. Note also that no reorganization was observed in the PTFEMA-SBMA membrane. Figure 13 shows that NaOH (水溶液) Both vitamin B12 and Na2SO4 after exposure to prevention The rate of vitamin B12 decreased prevention Note that the rate was more decreased compared to Na2SO4.

[0080] Membrane during filtration experiments of Examples 2A and 2B Permeability coefficient was consistently measured using a simple mass balance. The results of filtration experiments trapping 17 different uncharged / charged / dyed solutes are shown in Figure 14 (see Table 6 for a list of filtration IDs). The membrane flux was not affected during and after filtration with these solutes. This further implies that the underlying cause of the reorganization of the PTFEMA-SBMA-MAA membrane is the interaction with bases. [Table 6]

[0081] We also investigated how the base-reconstituted PTFEMA-SBMA-MAA-B1 membrane responded to basic solutions containing cations other than sodium and potassium (NaOH (水溶液) (containing sodium as a cation, whereas PBS contains sodium and potassium as cations). Since calcium is known to bind to carboxylates, it was thought that binding interactions might affect the membrane flux. In this experiment, a basic (pH = 10) solution of CaSO4 was used as a feed solution to measure the flux of the base-reconstituted PTFEMA-SBMA-MAA-B1 membrane. Permeability coefficient Figure 15 shows the results, which indicate that the recovery time of DIW flux is long, which is due to the interaction between cations and deprotonated MAA in the reconstituted PTFEMA-SBMA-MAA membrane. Permeability coefficient This suggests that the rate of decline will be Finally, preferred embodiments of the present invention are described in sections. [Embodiment 1] A copolymer comprising a plurality of zwitterionic monomer units, a plurality of charged / ionizable monomer units, and a plurality of hydrophobic monomer units. [Embodiment 2] 2. The copolymer of embodiment 1, wherein the molecular weight of the copolymer is from 20,000 g / mol to 1,000,000 g / mol. [Embodiment 3] 2. The copolymer of embodiment 1, wherein the molecular weight of the copolymer is from 40,000 g / mol to 1,000,000 g / mol. [Embodiment 4] 2. The copolymer of embodiment 1, wherein the molecular weight of the copolymer is from 100,000 g / mol to 1,000,000 g / mol. [Embodiment 5] 5. The copolymer of any one of the preceding embodiments, wherein the zwitterionic monomer units constitute 1 to 40% by weight of the copolymer. [Embodiment 6] 6. The copolymer of any one of the preceding embodiments, wherein the charged / ionizable monomeric units constitute 1 to 40% by weight of the copolymer. [Embodiment 7] 7. The copolymer according to any one of the preceding embodiments, wherein the hydrophobic monomer units constitute 30 to 80% by weight of the copolymer. [Embodiment 8] 8. The copolymer of any one of the preceding embodiments, wherein each of the zwitterionic monomer units is formed from a monomer comprising a sulfobetaine, a carboxybetaine, or a phosphorylcholine moiety. [Embodiment 9] 8. The copolymer of any one of the preceding claims, wherein each of the zwitterionic monomer units is formed from a monomer selected from the group consisting of sulfobetaine methacrylate (SBMA), methacryloxyphosphorylcholine (MPC), carboxybetaine methacrylate (CBMA), sulfobetaine-2-vinylpyridine, sulfobetaine-4-vinylpyridine, and sulfobetaine-vinylimidazole. [Embodiment 10] 8. The copolymer of any one of the preceding claims, wherein each of the zwitterionic monomer units is formed from sulfobetaine methacrylate (SBMA). [Embodiment 11] 11. The copolymer of any one of the preceding claims, wherein each of the charged / ionizable monomeric units is formed from a monomer selected from the group consisting of methacrylate, acrylate, acrylamide, or a styrene derivative containing a carboxylic acid, sulfonic acid, phosphoric acid, or amine moiety. [Embodiment 12] Each of the charged / ionizable monomeric units may be selected from the group consisting of methacrylic acid (MAA), acrylic acid, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, styrene sulfonate, 3-sulfopropyl acrylate, 3-sulfopropyl methacrylate, 2-acrylamido-2-methyl-1-propanesulfonic acid, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 2-aminoethyl methacrylate, [2-(methacryloyloxy)ethyl]trimethylammonium chloride, [2-(acryloyloxy)ethyl]trimethylammonium chloride, and [2-(acryloyloxy)ethyl]trimethylammonium chloride. 11. The copolymer of any one of embodiments 1 to 10, wherein the copolymer is formed from monomers selected from the group consisting of acryloyl-L-valine, (3-acrylamidopropyl)trimethylammonium chloride, N-[3-(dimethylamino)propyl]methacrylamide, 2-isopropenylaniline, 4-[N-(methylaminoethyl)aminomethyl]styrene, and (vinylbenzyl)trimethylammonium chloride. [Embodiment 13] 11. The copolymer of any one of the preceding embodiments, wherein each of the charged / ionizable monomeric units is formed from methacrylic acid (MAA). [Embodiment 14] 14. The copolymer of any one of embodiments 1 to 13, wherein each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of styrene, methyl methacrylate, acrylonitrile, fluoroalkyl acrylates, fluoroaryl acrylates, fluoroalkyl methacrylates, fluoroaryl methacrylates, fluoroalkyl acrylamides, and fluoroaryl acrylamides. [Embodiment 15] 14. The copolymer of any one of the preceding claims, wherein each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of 2,2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, and pentafluorophenyl methacrylate. [Embodiment 16] 14. The copolymer of any one of the preceding embodiments, wherein each of the hydrophobic monomer units is formed from 2,2,2-trifluoroethyl methacrylate (TFEMA). [Embodiment 17] 17. The copolymer according to any one of the preceding embodiments, wherein the hydrophobic monomer unit forms a homopolymer having a glass transition temperature above room temperature. [Embodiment 18] 18. The copolymer of any one of embodiments 1 to 17, wherein the copolymer is a linear copolymer; the copolymer is a statistical copolymer; the copolymer is a random copolymer; or the copolymer is a linear, statistical, or random copolymer. [Embodiment 19] 19. The copolymer according to any one of the preceding embodiments, wherein the copolymer is poly((sulfobetaine methacrylate)-random-(methacrylic acid)-random-(2,2,2-trifluoroethyl methacrylate)). [Embodiment 20] A polymer material comprising the copolymer according to any one of the first to nineteenth embodiments. [Embodiment 21] 21. The polymeric material of embodiment 20, wherein the polymeric material is in the form of a thin film. [Embodiment 22] 22. A composite membrane comprising a porous support and a thin film of the polymeric material of embodiment 21; the pore size of the porous support is larger than the pore size of the thin film of the polymeric material. [Embodiment 23] 23. The composite thin film of claim 22, wherein the thin film of the polymeric material has a thickness of from 1 nm to 10 μm. [Embodiment 24] 23. The composite thin film of claim 22, wherein the thin film of the polymeric material has a thickness of from 1 nm to 3 μm. [Embodiment 25] 23. The composite thin film of claim 22, wherein the thin film of the polymeric material has a thickness of from 1 nm to 1 μm. [Embodiment 26] 26. A composite membrane according to any one of embodiments 22 to 25, wherein the membrane of the polymeric material has an effective pore size of from 0.1 nm to 5 nm. [Embodiment 27] 26. A composite membrane according to any one of embodiments 22 to 25, wherein the membrane of the polymeric material has an effective pore size of from 0.6 nm to 3 nm. [Embodiment 28] 26. A composite thin film according to any one of embodiments 22 to 25, wherein the thin film of polymeric material has an effective pore size of from 0.6 nm to 2 nm. [Embodiment 29] 29. The composite membrane of any one of embodiments 22 to 28, wherein the composite membrane exhibits resistance to fouling by oil emulsions. [Embodiment 30] 30. The composite film of any one of embodiments 22 to 29, wherein the composite film is stable upon exposure to chlorine bleach (e.g., pH 4). [Embodiment 31] 31. The composite membrane of any one of embodiments 22 to 30, wherein the composite membrane undergoes a one-time irreversible change in pore size upon exposure to a high pH buffer. [Embodiment 32] 32. The composite membrane of any one of embodiments 22 to 31, wherein the composite membrane exhibits size-based selectivity between uncharged organic molecules. [Embodiment 33] The composite thin film contains charged solutes and salts. prevention 33. The composite thin film according to any one of embodiments 22 to 32. [Embodiment 34] A method for size-based selection or removal comprising contacting a solution containing a plurality of uncharged organic molecules of different sizes with a composite thin film according to any one of embodiments 22 to 33. [Embodiment 35] A method of charge-based selection or removal comprising contacting a solution containing a plurality of salts with the composite film of any one of embodiments 22 to 33.

[0082] 1. Asatekin Alexiou,A.;Bengani,P. Zwitterion Containing Membranes. US Application 61901624,2013. 2. Bengani, P.; Kou, Y.; Asatekin, A., Zwitterionic copolymer self-assembly for fouling resistant, high flux membranes with size-based small molecule selectivity. Journal of Membrane Science 2015,493,755-765. 3. Bengani-Lutz, P.; Asatekin Alexiou, A. Fabrication of filtration membranes. Patent application 62 / 416,340,November 2,2016,filed 2016. 4. Bengani-Lutz, P.; Converse, E.; Cebe, P.; Asatekin, A., Self-Assembling Zwitterionic Copolymers as Membrane Selective Layers with Excellent Fouling Resistance:Effect of Zwitterion Chemistry. ACS Applied Materials & Interfaces 2017,9(24),20859-20872. 5. Bengani-Lutz,P.;Zaf,R.D.;Culfaz-Emecen,P.Z.;Asatekin,A.,Extremely fouling resistant zwitterionic copolymer membranes with ~ Inm pore size for treating municipal,oily and textile wastewater streams. Journal of Membrane Science 2017,543(Supplement C),184-194. 6. Sadeghi,I.;Asatekin,A.,Spontaneous Self-Assembly and Micellization of Random Copolymers in Organic Solvents. Macromolecular Chemistry and Physics 2017,218 (20),1700226. 7. Sadeghi,I.;Asatekin,A.,Membranes with Functionalized Nanopores for Aromaticity-Based Separation of Small Molecules. ACS Applied Materials & Interfaces 2019,11(13),12854-12862. 8. Asatekin Alexiou,A.;Sadeghi,I. Two-layer nanofiltration membranes. Patent application 62 / 131,001,March 10,2015,2015. 9. Ji,Y.L.;An,Q.F.;Zhao,Q.;Sun,W.D.;Lee,K.R.;Chen,H.L.;Gao,C.I,Novel composite nanofiltration membranes containing zwitterions with high permeate flux and improved anti-fouling performance. Journal of Membrane Science 2012,390,243-253. 10. Petersen,R.J.,Composite Reverse Osmosis and Nanofiltration Membranes. Journal of Membrane Science 1993,S3(1),81-150. 11. Bengani-Lutz,P. Zwitterionic Copolymer Self-assembly for Fouling Resistant,High Flux Membranes with Small Molecule Selectivity. Ph.D.Thesis,Tufts University,2017.< / high>

Claims

1. 1. A composite membrane comprising a porous support and a membrane of a polymeric material, the pore size of the porous support is greater than the pore size of the thin film of polymeric material; The polymeric material comprises: A plurality of zwitterionic monomer units, a plurality of charged / ionizable monomeric units, and Multiple hydrophobic monomer units The copolymer comprises The composite thin film, wherein the copolymer is a linear statistical and random copolymer.

2. 2. The composite membrane of claim 1, wherein the copolymer has a molecular weight of 20,000 g / mol to 1,000,000 g / mol.

3. 2. The composite membrane of claim 1, wherein the molecular weight of the copolymer is from 40,000 g / mol to 1,000,000 g / mol.

4. 2. The composite membrane of claim 1, wherein the molecular weight of the copolymer is from 100,000 g / mol to 1,000,000 g / mol.

5. A composite membrane according to any one of claims 1 to 4, wherein the zwitterionic monomer units constitute from 1 to 40% by weight of the copolymer.

6. A composite membrane according to any one of claims 1 to 5, wherein the charged / ionizable monomeric units constitute 1 to 40% by weight of the copolymer.

7. A composite membrane according to any one of claims 1 to 6, wherein the hydrophobic monomer units constitute 30 to 80% by weight of the copolymer.

8. 8. The composite thin film of claim 1, wherein each of the zwitterionic monomer units is formed from a monomer comprising a sulfobetaine, a carboxybetaine, or a phosphorylcholine moiety.

9. 8. The composite thin film of claim 1, wherein each of the zwitterionic monomer units is formed from a monomer selected from the group consisting of sulfobetaine methacrylate (SBMA), methacryloxyphosphorylcholine (MPC), carboxybetaine methacrylate (CBMA), sulfobetaine-2-vinylpyridine, sulfobetaine-4-vinylpyridine, and sulfobetaine-vinylimidazole.

10. 8. The composite thin film of claim 1, wherein each of the zwitterionic monomer units is formed from sulfobetaine methacrylate (SBMA).

11. 11. The composite thin film of any one of claims 1 to 10, wherein each of the charged / ionizable monomeric units is formed from a monomer selected from the group consisting of methacrylate, acrylate, acrylamide, or styrene derivatives containing a carboxylic acid, sulfonic acid, phosphoric acid, or amine moiety.

12. Each of the charged / ionizable monomeric units is selected from the group consisting of methacrylic acid (MAA), acrylic acid, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, styrene sulfonate, 3-sulfopropyl acrylate, 3-sulfopropyl methacrylate, 2-acrylamido-2-methyl-1-propanesulfonic acid, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 2-aminoethyl methacrylate, [2-(methacryloyloxy)ethyl]trimethylammonium chloride, [2-(acryloyloxy)ethyl]trimethylammonium chloride, and [2-(acryloyloxy)ethyl]trimethylammonium chloride.

11. The composite thin film of claim 1, wherein the composite thin film is formed from monomers selected from the group consisting of N-acryloyl-L-valine, (3-acrylamidopropyl)trimethylammonium chloride, N-[3-(dimethylamino)propyl]methacrylamide, 2-isopropenylaniline, 4-[N-(methylaminoethyl)aminomethyl]styrene, and (vinylbenzyl)trimethylammonium chloride.

13. A composite membrane according to any one of claims 1 to 10, wherein each of the charged / ionizable monomeric units is formed from methacrylic acid (MAA).

14. 14. The composite thin film of any one of claims 1 to 13, wherein each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of styrene, methyl methacrylate, acrylonitrile, fluoroalkyl acrylates, fluoroaryl acrylates, fluoroalkyl methacrylates, fluoroaryl methacrylates, fluoroalkyl acrylamides, and fluoroaryl acrylamides.

15. 14. The composite thin film of any one of claims 1 to 13, wherein each of the hydrophobic monomer units is formed from a monomer selected from the group consisting of 2,2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, and pentafluorophenyl methacrylate.

16. A composite membrane according to any one of claims 1 to 13, wherein each of the hydrophobic monomer units is formed from 2,2,2-trifluoroethyl methacrylate (TFEMA).

17. A composite membrane according to any one of claims 1 to 16, wherein the hydrophobic monomer units form homopolymers having a glass transition temperature above room temperature.

18. 18. A composite membrane according to any one of claims 1 to 17, wherein the copolymer is poly((sulfobetaine methacrylate)-random-(methacrylic acid)-random-(2,2,2-trifluoroethyl methacrylate)).

19. A composite thin film according to any preceding claim, wherein the thin film of polymeric material has a thickness of from 1 nm to 10 μm.

20. A composite membrane according to any preceding claim, wherein the membrane of polymeric material has a thickness of from 1 nm to 3 μm.

21. A composite thin film according to any preceding claim, wherein the thin film of polymeric material has a thickness of from 1 nm to 1 μm.

22. A composite membrane according to any preceding claim, wherein the membrane of polymeric material has an effective pore size of from 0.1 nm to 5 nm.

23. A composite membrane according to any preceding claim, wherein the membrane of polymeric material has an effective pore size of from 0.6 nm to 3 nm.

24. A composite membrane according to any preceding claim, wherein the membrane of polymeric material has an effective pore size of from 0.6 nm to 2 nm.

25. A composite membrane according to any preceding claim, exhibiting resistance to fouling by oil emulsions.

26. A composite thin film according to any one of claims 1 to 25 which is stable when exposed to chlorine bleach.

27. 27. A composite membrane according to any one of claims 1 to 26, which undergoes a one-time irreversible change in pore size upon exposure to a high pH buffer.

28. A thin composite membrane according to any one of claims 1 to 27, which exhibits size-based selectivity between uncharged organic molecules.

29. A composite membrane according to any one of claims 1 to 28, which exhibits rejection of charged solutes and salts.

30. A method for size-based selection or removal comprising contacting a solution containing a plurality of uncharged organic molecules of different sizes with a thin composite film according to any one of claims 1 to 29.

31. A method of charge-based selection or removal comprising contacting a solution containing a plurality of salts with the composite film of any one of claims 1 to 29.